2021
DOI: 10.3390/metabo11030153
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Gut as a Potential Culprit for the Paradoxical Dysglycemic Response to Gastric Bypass-Associated Ileal Microbiota

Abstract: Altered host-intestinal microbiota interactions are increasingly implicated in the metabolic benefits of Roux-en-Y gastric bypass (RYGB) surgery. We previously found, however, that RYGB-associated ileal microbiota can paradoxically impair host glycemic control when transferred to germ-free mice. Here we present complementary evidence suggesting that this could be due to the heightened development of systemic endotoxemia. Consistently, application of ileal content from RYGB-treated compared with sham-operated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…More recent research has not supported the hypothesis; a transfer of gut microbiota from the caecum of rats following RYGB surgery into germ-free mice failed to produce a difference in percentage body fat gain despite the successful establishment of transplanted microbiota [18]. Another similar study in 2021 transferred colonic microbiota from rats six weeks after RYGB surgery into germ-free mice and reported that body weights were similar between recipient groups [19]. A well-described recent study in 2022 transplanted the faecal microbiota from human patients before and after two different types of gastric weight loss surgery into mice with differences in particular bacterial genera between different groups of recipient mice [20].…”
Section: Microbiota Transplantation Following Gastric Bypass Surgerymentioning
confidence: 99%
“…More recent research has not supported the hypothesis; a transfer of gut microbiota from the caecum of rats following RYGB surgery into germ-free mice failed to produce a difference in percentage body fat gain despite the successful establishment of transplanted microbiota [18]. Another similar study in 2021 transferred colonic microbiota from rats six weeks after RYGB surgery into germ-free mice and reported that body weights were similar between recipient groups [19]. A well-described recent study in 2022 transplanted the faecal microbiota from human patients before and after two different types of gastric weight loss surgery into mice with differences in particular bacterial genera between different groups of recipient mice [20].…”
Section: Microbiota Transplantation Following Gastric Bypass Surgerymentioning
confidence: 99%
“…For example, a study on Zucker fatty rats found that RYGB causes major shifts in the microbiota across the small and large intestine [37]. Interestingly, transplanting ileal microbiota from RYGB-operated rats to germ-free mice worsened oral glucose tolerance [37], likely due to the generation of metabolites that disrupt the intestinal epithelial barrier and trigger systemic endotoxemia [38]. On the other hand, transplanting colonic microbiota of RYGB-operated rats to germ-free mice improved oral glucose tolerance, possibly by stabilizing the intestinal epithelial barrier through increased bile acid receptor FXR signaling via the generation of secondary bile acids [39].…”
Section: Intestinal Milieumentioning
confidence: 99%
“…Reminiscent of the studies of Blanchard et al [6] and Jin et al [8], ileal content of RYGB-treated rats caused the opposite effect of content from the other gut regions. That is, it increased paracellular permeability in Caco-2 cells and heightend endotoxemia in germ-free mice [10]. The former effect was associated with a strong reduction in the tight junction protein claudin-4 and the adherens junction protein desmoglein-2 [10] in Caco-2 cells.…”
mentioning
confidence: 99%
“…That is, it increased paracellular permeability in Caco-2 cells and heightend endotoxemia in germ-free mice [10]. The former effect was associated with a strong reduction in the tight junction protein claudin-4 and the adherens junction protein desmoglein-2 [10] in Caco-2 cells. The implications of these findings are unclear, but raise the possiblity that during relapse of type 2 diabetes in the significant proportion of patients after RYGB the barrier-disruptive ileal microbiota expand thereby exerting a dominant (negative) effect on endotoxemia (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation